16=8(f+26)

Simple and best practice solution for 16=8(f+26) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 16=8(f+26) equation:


Simplifying
16 = 8(f + 26)

Reorder the terms:
16 = 8(26 + f)
16 = (26 * 8 + f * 8)
16 = (208 + 8f)

Solving
16 = 208 + 8f

Solving for variable 'f'.

Move all terms containing f to the left, all other terms to the right.

Add '-8f' to each side of the equation.
16 + -8f = 208 + 8f + -8f

Combine like terms: 8f + -8f = 0
16 + -8f = 208 + 0
16 + -8f = 208

Add '-16' to each side of the equation.
16 + -16 + -8f = 208 + -16

Combine like terms: 16 + -16 = 0
0 + -8f = 208 + -16
-8f = 208 + -16

Combine like terms: 208 + -16 = 192
-8f = 192

Divide each side by '-8'.
f = -24

Simplifying
f = -24

See similar equations:

| 61=x-7x+7 | | 4y-8y+6=26 | | -2x-3-3x=-33 | | (x-3-3i)*(x-3+3i)= | | 0=x^2+4x+12 | | x^2+7x=68.75 | | 5x+2y+2=11+9y-x | | 13-ln(5-x)=0 | | 7=5v-19 | | -54=7x+3x+6 | | 2x-4=(2x-9)/2 | | -12=-6j | | 2g-11(-2)=26 | | 0=-6x-2x-8 | | Dy=Cx | | 4/3t=5/2 | | -6x-9+2x=39 | | (3t^2-t-4)(4t^2+3t-1)= | | 2x+5+3x=-25 | | 3(13+5.5k)=6k+18 | | 33=-4x-3x-2 | | -2-3x-4x=33 | | Cot^4x-1=0 | | 2-3x-4x=33 | | 2x^2+6y^2=13 | | 49/7p-49 | | 4[lnz+ln(z+5)]-2ln(z-5)= | | h=-16t*t+128t | | 4+6x+6x=-44 | | 1+7x+2x=109 | | 7(c-9)=9(2c-8)-4c | | 9x^6y^10/x^0Y^9 |

Equations solver categories